The Years of Jesuit Suppression, 1773–1814: Survival, Setbacks, and Transformation - Shore, Paul (Brill research perspectives in Jesuit studies, 2020)
The forty-one years between the Society of Jesus’s papal suppression in 1773 and its eventual restoration in 1814 remain controversial, with new research and interpretations continually appearing. Shore’s narrative approaches these years, and the period preceding the suppression, from a new perspective that covers individuals not usually discussed in works dealing with this topic. As well as examining the contributions of former Jesuits to fields as diverse as ethnology—a term and concept pioneered by an ex-Jesuit—and library science, where Jesuits and ex-Jesuits laid the groundwork for the great advances of the nineteenth century, the essay also explores the period the exiled Society spent in the Russian Empire. It concludes with a discussion of the Society’s restoration in the broader context of world history.